2016
DOI: 10.5858/arpa.2015-0167-cp
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Irradiation Practice for the Prevention of Transfusion-Associated Graft-versus-Host Disease

Abstract: Context.—Transfusion-associated graft-versus-host disease is a rare, often fatal complication of cellular blood product transfusion. The requirement that at-risk groups receive irradiated products reduces the incidence of transfusion-associated graft-versus-host disease. A comprehensive survey of irradiation practices has not been performed since 1989; meanwhile, new indications for irradiation have emerged. Objective.—To assess current irradiation practices at College of American Pathologists m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Gamma irradiation of RBCs is practiced widely across the world to protect the transfused immunocompromised patients from the potentially life‐threatening complication of transfusion‐associated GVHD . Recent in vitro studies have shown that the storage lesion is exacerbated by gamma irradiation and that it worsens during subsequent storage .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma irradiation of RBCs is practiced widely across the world to protect the transfused immunocompromised patients from the potentially life‐threatening complication of transfusion‐associated GVHD . Recent in vitro studies have shown that the storage lesion is exacerbated by gamma irradiation and that it worsens during subsequent storage .…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants are intrinsically immunocompromised. Therefore, gamma irradiation of leukoreduced RBCs is used to prevent transfusion‐associated graft‐versus‐host disease (GVHD) . However, gamma irradiation also exacerbates “storage lesion” formation and accelerates biochemical, structural, and rheologic changes in stored RBCs …”
mentioning
confidence: 99%
“…42 A 2014 College of American Pathologists survey of practices at approximately 2100 US institutions revealed that 1) many institutions are not routinely irradiating units for immunocompromised patient groups known to be at risk for TA-GVHD (only 36%-63% performed irradiation across various at-risk disease categories), 2) immunocompetent patients routinely receive irradiated components only when the donor is known to be a blood relative, and 3) there is substantial interinstitutional variation. 97 A minority (2.6%) of institutions had more stringent policies including universal irradiation of all transfused cellular components or "block" irradiation for all patients on a given service/floor or for very young patients due to undiagnosed congenital immunodeficiency. Thus, the College of American Pathologists survey indicates that different US institutions implicitly tolerate different levels of risk for TA-GVHD.…”
Section: Overall Policy and Practical Issues In Deciding On A Methods mentioning
confidence: 99%
“…There are variances in initiation and discontinuation of providing irradiated blood products to this patient population. 33 There is no evidence as to when irradiation may be safely discontinued in this patient population. 28 Transfusion service specialists (blood bank director, transfusion medicine consultant, etc) should be available for consultation.…”
Section: 25mentioning
confidence: 99%
“…26 A 2014 survey conducted by the College of American Pathologists demonstrated that the 3 most common indications for blood product irradiation were ''transfusion from blood relatives'' (78.6%), ''HLA-matched or partially matched products'' (68.9%), and ''neonatal exchange transfusion'' (66.3%). 33 These numbers are worrisome because general guidance requires universal irradiation (100%) for these indications, but depending on the scenario, 21.4% to 33 …”
Section: Regulationsmentioning
confidence: 99%